Pengaruh Pengendalian Internal Terhadap Kinerja Karyawan Pada Bank Perkreditan Rakyat Karya Remaja Kabupaten Indramayu Cabang Kecamatan Krangkeng - Amsorih .; Imam Subaweh (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
This study aims to examine the effect of internal control on employee performance at Bank BPR Karya Remaja, Indramayu Regency, Krangkeng District Branch. Specifically, this study analyzes five main components of internal control, namely the effect of general internal control, risk assessment, control activities, information and communication, and supervisory activities on employee performance. This study uses a descriptive quantitative research approach and multiple linear regression analysis. The data collection technique was taken through a questionnaire with a sample in this study taking 30 employees who work at Bank Perkreditan Rakyat Karya Remaja, Krangkeng District in the 2020-2025 period. The sampling method uses non-probability sampling with a purposive sampling technique. The results of the t-test show that the variables of internal control, risk assessment, control activities, information and communication, supervisory activities partially have a significant effect on the Employee Performance variable. The results of the F test show that the variables of Control, risk assessment, control activities, information and communication, supervisory activities simultaneously or together have an effect on employee performance.